Assessing the Economic Potential of Banana Production on Critical Land in Plandaan Sub-District, Jombang Regency - Zulfikar Zulfikar; Siti Nur Qomariyah; Dede Ahmad Huzeni (Sigmagri, 2022)
Banana fruit productivity on critical land, although it has limited land capacity, has economic potential if the regional potential is developed. This study aims to determine the economic potential of banana production by measuring the level of efficiency and farm income on critical land in Plandaan sub-District, Jombang Regency. This research was conducted using a survey method with the determination of sample villages using the Simple Random Sampling method, as many as 39 people were sampled. The results of this study indicate that banana fruit farming per hectare requires a production cost of Rp. 31,010,000 with a gross income of Rp. 58,500,000, so the net income is Rp. 27,490,000. The results of the analysis of the R/C Ratio obtained that the efficiency level of banana fruit farming on 1 Ha land was 1.886 which showed a profit. This means that banana fruit farming in Plandaan District, Jombang Regency is feasible to be developed.